2001
DOI: 10.3758/bf03194436
|View full text |Cite
|
Sign up to set email alerts
|

Covariation in individuals’ sensitivities to bitter compounds: Evidence supporting multiple receptor/transduction mechanisms

Abstract: People vary widely in their sensitivities to bitter compounds, but the intercorrelation of these sensitivities is unknown. Our goal was to investigate correlations as a function of individual sensitivities to several bitter compounds representative of different chemical classes and, from these correlations, infer the number and variety of potential bitterness transduction systems for these compounds. Twenty-six subjects rated and ranked quinine HCl, caffeine, (-)-epicatechin, tetralone, L-phenylalanine, L-tryp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

12
100
2

Year Published

2002
2002
2020
2020

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 139 publications
(114 citation statements)
references
References 48 publications
12
100
2
Order By: Relevance
“…Some of the frequently tested bitter compounds include quinine (found in the bark of the cinchona tree and used to treat malaria), caffeine (found in coffee beans and widely consumed for its stimulant properties), epicatechin (found in tea), tetralone (found in hops and, by extension, in beer), l-phenylalanine (an amino acid), magnesium sulfate (a mineral found in Epsom salts), urea (a product of nitrogen metabolism), naringin (a compound found in grapefruit), sucrose octaacetate (an acetylated derivative of sucrose), denatonium benzoate (used in consumer products to discourage accidental poisoning), and propylthiouracil (a sulfur-containing drug used to treat hyperthyroid disease). People exhibit marked differences in perceiving these chemicals 18,35,36 : Some find bitter compounds to be very bitter, whereas others experience the same concentration of the same chemical as much less intense.…”
Section: Bitter: Poisoned With Pleasurementioning
confidence: 99%
See 1 more Smart Citation
“…Some of the frequently tested bitter compounds include quinine (found in the bark of the cinchona tree and used to treat malaria), caffeine (found in coffee beans and widely consumed for its stimulant properties), epicatechin (found in tea), tetralone (found in hops and, by extension, in beer), l-phenylalanine (an amino acid), magnesium sulfate (a mineral found in Epsom salts), urea (a product of nitrogen metabolism), naringin (a compound found in grapefruit), sucrose octaacetate (an acetylated derivative of sucrose), denatonium benzoate (used in consumer products to discourage accidental poisoning), and propylthiouracil (a sulfur-containing drug used to treat hyperthyroid disease). People exhibit marked differences in perceiving these chemicals 18,35,36 : Some find bitter compounds to be very bitter, whereas others experience the same concentration of the same chemical as much less intense.…”
Section: Bitter: Poisoned With Pleasurementioning
confidence: 99%
“…But it is important to put these details in context. Although people differ in their ability to taste many bitter chemicals, 36 the complete loss of bitter perception for a particular chemical like PTC is probably rare. (It might be misleading to call this a complete loss because the nontaster form of the receptor might detect different bitter molecules.…”
Section: Bitter: Poisoned With Pleasurementioning
confidence: 99%
“…Whereas some studies indicate that bitter taste processing is, depending on the substances tested, not uniform (McBurney et al, 1972;Whitney and Harder, 1994;Dahl et al, 1997;Delwiche et al, 2001;Frank et al, 2004), other studies concluded that purely bitter tasting compounds cannot be distinguished (Spector and Kopka, 2002).…”
Section: Introductionmentioning
confidence: 99%
“…Large variations between individuals have been observed in their perception of bitter tastes. Delwiche et al (2001) for example, reported between-subject differences in the perceived suprathreshold intensities of a variety of chemically diverse bitter compounds of up to two orders of magnitude. Furthermore, individuals vary substantially in their relative sensitivities to different bitter stimuli (Delwiche et al, 2001;Yokomukai et al, 1993).…”
Section: Producer Assessment Of Style and Phenol Concentrationmentioning
confidence: 99%
“…Delwiche et al (2001) for example, reported between-subject differences in the perceived suprathreshold intensities of a variety of chemically diverse bitter compounds of up to two orders of magnitude. Furthermore, individuals vary substantially in their relative sensitivities to different bitter stimuli (Delwiche et al, 2001;Yokomukai et al, 1993). Every extra virgin olive oil contains a unique mix of different phenol species, with each species eliciting different degrees of bitterness and pungency (Gutiearrez-Rosales et al, 2003;Andrewes et al, 2003).…”
Section: Producer Assessment Of Style and Phenol Concentrationmentioning
confidence: 99%